The impact of hearing loss on speech outcomes in 5-year-old children with cleft palate ± lip: A longitudinal cohort study. (October 2021) - Fitzpatrick, Beth; Panagamuwa, Channa; Moss Levy, Leora; Rihtman, Tanya
Abstract: Objectives: To investigate the impact of hearing loss (using longitudinal measurements of hearing) on speech outcomes at age 5 (5 years 0 months–5 years 11 months) in children born with cleft palate ± lip. Other variables which may impact upon the speech outcomes at age 5 in this population were also investigated. Methods: A retrospective longitudinal cohort study of children, without a named syndrome, born with cleft palate ± lip, and treated at a Cleft Centre in the United Kingdom. Data collected from infancy to 5 years 11 months, included hearing test results from three specific time points (7 months–1 year 2 months [age A]; 2 years 0 months–2 years 11 months [age B]; 5 years 0 months–5 years 11 months [age C]) and speech outcome data at age 5 years (5 years 0 months–5 years 11 months). Hearing test results at each age were compared to identify how hearing changes with age. Correlations between hearing test results and speech outcomes at age 5 were analysed. Results: Hearing loss was frequent but predominantly mild. There were no significant correlations between speech outcomes and hearing results at any age. Mild hearing loss remained prevalent at age 5, although a significant age-related hearing improvement was found. A significant relationship between cleft type and cleft speech characteristics was found (P < .001); children with Bilateral Cleft Lip and Palate achieved the poorest articulation outcomes. Conclusion: Although mild hearing loss was common in the cohort, there was no association between hearing loss and the speech outcomes investigated. In contrast, the type of cleft was significantly associated with the presence of cleft speech characteristics. Further longitudinal measurement of hearing is required to substantiate the findings of this study. Highlights: Hearing significantly improves with age in the cleft palate ± lip population. Mild hearing loss did not impact speech outcomes at age 5. Children with Bilateral Cleft Lip and Palate have the poorest speech outcomes at age 5.